Analyzing The Impact Of Job Stress, Job Insecurity, and Work Engagement On Job Performance During The COVID-19 Pandemic In The Aviation Industry (School of Business and Management Institut Teknologi Bandung, 2022)
Abstract. The COVID-19 pandemic has devastated the global airline industry. In Indonesia alone, the industry suffered USD 8.225 billion loss in revenue and recorded a 50% drop in passenger demand in 2020 compared to the previous year. The low demand for air travel and no clear end to the pandemic has caused a double crisis, health and economic, affecting aviation industry employees on a personal level. This research aims to determine the impact of perceived COVID-19 pandemic concerns on job stress, work engagement, and job insecurity among aviation industry employees. It further explores the pandemic’s impact on job performance. Using structural equation modeling (SEM) based on partial least squares (PLS), the research examined the data of aviation industry employees who work for various companies, including airlines, airports, and the Maintenance Repair Organization (MRO) in Indonesia. The results of this research show that perceived pandemic concerns create another layer of job insecurity and job stress and negatively impact work engagement. Work engagement positively impacts job performance. Therefore, as a result, perceived pandemic concerns have an indirect positive impact on job performance. Keywords: Aviation Industry, COVID-19 Pandemic, Employment Uncertainty, Job Performance.